Dynamic Stochastic General Equilibrium (DSGE) Models in the Modern Monetary Policy - Aleksandra NOCOŃ (Communications of International Proceedings, 2023)
The paper undertakes the issue of DSGE models in the modern monetary policy. Although DSGE models are broad used by central banks since 1980s of the 21st century, the main motivation to undertake this topic was to systematize the current knowledge about this type of models. Many publications concentrate on DSGE models, however they do not provide a holistic information about their construction, evolution as well as pros and cons. This paper provides all these things in more comprehensive form. The paper has theoretical nature and based mainly on literature studies, documental analysis method and synthesis method. The main aim of the article is to systematize the current state of knowledge in the field of DSGE models, as well as to assess their role in modern monetary policy. Therefore, the article has a theoretical character, is a kind of review presenting the evolution of early DSGE models, general assumptions and characteristics of modern DSGE models, as well as main advantages and disadvantages from the perspective of their application in monetary policy. At the end of the paper the current forecasting model of the Federal Reserve System was presented. The paper indicated that DSGE models are currently one of the main classes of macroeconomic models used in modern monetary policy.
Keywords: DSGE model; modern central bank; monetary policy modelling